1966
DOI: 10.2135/cropsci1966.0011183x000600040012x
|View full text |Cite
|
Sign up to set email alerts
|

Malting Quality in F1 Hybrids of Barley1

Abstract: Seed of 8 varieties of barley and all possible F1 hybrids from crosses among the varieties were malted to obtain data on 8 malting quality characters. On the average, significant heterosis as measured from the mid‐parents was observed in the F1 hybrids for percent extract, percent malt nitrogen, and percent plump kernels. The F1 hybrid average for percent extract was intermediate between the mid‐parent and high‐parent average. F1 hybrid averages for percent malt nitrogen and percent plump kernels were similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
1989
1989

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Suneson and Dickson (1966) reported that hybrids were intermediate between the parents for most malting quality characters except for protein, which was lower and in the preferred direction. Rasmusson et al (1966) found that only 7 of 28 hybrids were acceptable for all of 8 malting quality characters. Six of the acceptable hybrids had an acceptable malting cultivar as one parent.…”
Section: Performance Of Hybrid Barleymentioning
confidence: 98%
See 1 more Smart Citation
“…Suneson and Dickson (1966) reported that hybrids were intermediate between the parents for most malting quality characters except for protein, which was lower and in the preferred direction. Rasmusson et al (1966) found that only 7 of 28 hybrids were acceptable for all of 8 malting quality characters. Six of the acceptable hybrids had an acceptable malting cultivar as one parent.…”
Section: Performance Of Hybrid Barleymentioning
confidence: 98%
“…In their studies, heterosis in FI yield was indicated as due to overdominance, but the reduced heterosis that was observed in F2 yield indicated a lack of overdominance. Rasmusson et al (1966) reported that malting quality in F I hybrids appeared to depend largely on the frequency of favorable genes with additive effects, although for percent extract, percent plump kernels and percent malt nitrogen, there was evidence for genes having dominance and/or epistatic effects.…”
Section: Base Of Heterosis In Barleymentioning
confidence: 99%